A Study on Developing the Kadazandusun Commercial and Industrial Community (KCIC) in Sabah, Malaysia - Tanakinjal, Geoffrey Harvey (1999)
The creation of a Bumiputera Commercial and Industrial Community was formulated to achieve the second strategy of the New Economic Policy, which was removing the identification of race with major economic function. Through this concept an exploratory research on the creation of a Kadazandusun Commercial and Industrial Community was made to enable the Kadazandusun community to be at par with other communities by the year 2020. The first two objectives of this study determined the current level of involvement of the Kadazandusun in commercial and industrial activities and identifying current entrepreneurship development programmes. From the secondary data, the Kadazandusun controls less than 17 percent of the 9 economic sectors used as a basis for comparison for current economic performance and were not aware of entrepreneurship development programmes. In accessing the strengths, wealmesses, opportunities and threats facing the community a questionnaire survey was cond ucted . Data processing included both qualitative and quantit.ative method. Five groups representing the cultural community characteristics namely awareness, information: psychological> culture and manpower development were identified through factor analysis and acted as independent variables towards community's information awareness, knowledge regarding available loans, administration and management, networking, market share, manpower development and financial management in the regression analysis. Using situational analysis, Strategic factors Analysis Summary Matrix revealed strategic factors for the development of Kadazandusun community. Strategic strength factors were "Bumiputera Status", "Largest Bumiputera Group" and "Government Development Programmes", while the major weaknesses were "Motivation", "Access to Business Information", and "Management Skills". Whereas opportunities were represented by "Kota Kinabalu Industrial Park", "Access to Loans" and "Government Policies". The threat factors were "Competition from Other Communities", and "poatics".An "lnformation Center" was recommended to be set-up by the Kadazandusun Chamber of Commerce and lndustry to help entrepreneurs in terms of management skills, financial management, information management, quality development, strategic networking, business development, technology development and fulfilling human resources needs. Institutions dealing in business consultancy, entrepreneurship development programme, information technology, training and funding were also recommended in the proposed model. These key factors will- produced genuine entrepreneurs of quality and resilient to challenges, competitive in all potential area of economic growth, able to cultivate entrepreneurship culture, and capable of developing and nurturing the Kadazandusun community's capabilities in businesses and pursue the nation's industrialisation's goals as envisaged in Vision 2020.